Is Having Inflammatory Bowel Disease a Risk Factor for Severe Acute Respiratory Syndrome Coronavirus 2? - Çavuş, Bilger; Akyüz, Filiz; Örmeci Çifçibaşı, Aslı; Özgür, İlker; Erel, Cansu; Yakut, Aysun; İmanov, Ziya; Şenkal, İbrahim Volkan; Medetalibeyoğlu, Alpay; Köse, Murat; Keskin, Metin; Demir, Kadir; et al. (Turkish Journal of Gastroenterology, 2022)
Background: The severe acute respiratory syndrome coronavirus 2 virus was found to have effects not only in the lungs but also inmany different organs. We aimed to evaluate the management of our patients with inflammatory bowel disease in this pandemic, theincidence of coronavirus disease 2019 in terms of clinical, medical treatment, and features of inflammatory bowel disease, and to investigate the effects of the severe acute respiratory syndrome coronavirus 2 on this particular group of patients.Methods: During the coronavirus disease 2019 pandemic, 207 patients who had inflammatory bowel disease for at least 6 months werequestioned for coronavirus disease 2019 at their outpatient clinic admissions, and their medical records were evaluated prospectively.Results: Of the 207 patients, 146 had Crohn’s disease. The mean disease duration was determined as 118.15 ± 72.85 months. Of thepatients, 127 (61.4%) were using mesalazine, 110 (53.1%) azathioprine, and 148 (71.5%) biological agents. It was found that 66 (31.9%)patients changed their medications during the coronavirus disease 2019 pandemic. As a medication change, anti-Tumor NecrosisFactor (TNF) dose was observed to be omitted most frequently at a rate of 80%. Diarrhea was present in 20.8%, abdominal pain in20.3%, nausea in 10.6%, anorexia in 13.5%, and weight loss in 15.9% of the patients. Twelve (5.79%) patients were diagnosed withcoronavirus disease 2019. Lung involvement was present in 11 (91.7%) of the patients diagnosed with coronavirus disease 2019. Of thepatients diagnosed and not diagnosed with coronavirus disease 2019, 75% vs. 71.6% were using biological agents (P = .80), respectively.Half of the patients diagnosed with coronavirus disease 2019 were active in terms of inflammatory bowel disease at the time of diagnosis, and 2 of these patients were severely active.Conclusion: The incidence of coronavirus disease 2019 infection in patients with inflammatory bowel disease was not different from thegeneral population during the severe acute respiratory syndrome coronavirus 2 pandemic. Coronavirus disease 2019 infection does notprogress with poor prognosis in patients with inflammatory bowel disease who receive immunosuppressive therapy including biologicalagents